1993
DOI: 10.1002/hep.1840170322
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor and Liver Disease

Abstract: A working formulation for the role of ANF in the sodium retention of cirrhosis is summarized in Figure 4. Sodium retention is initiated early in cirrhosis, either as a result of hepatic venous outflow block or of primary vasodilation. The consequent intravascular volume expansion causes increases in ANF levels. At this stage of disease, the rise in ANF level is sufficient to counterbalance the antinatriuretic influences. However, this occurs at the expense of an expanded intravascular volume with the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…(3) The plasma levels of atrial natriuretic peptide, a peptide released from the heart with potent vasodilator properties, are markedly higher in patients with type 1 compared with those in patients with type 2 HRS. The actual pathogenic significance of increased atrial natriuretic peptide levels in cirrhosis is unknown, but a role as mediator of splanchnic arterial vasodilation or antagonist of the effects of vasoconstrictor systems in the kidney has been proposed 48, 49. Taken together, these findings indicate that changes in the systemic arterial circulation of patients with type 1 and type 2 HRS are qualitatively similar but of different intensity.…”
Section: Discussionmentioning
confidence: 90%
“…(3) The plasma levels of atrial natriuretic peptide, a peptide released from the heart with potent vasodilator properties, are markedly higher in patients with type 1 compared with those in patients with type 2 HRS. The actual pathogenic significance of increased atrial natriuretic peptide levels in cirrhosis is unknown, but a role as mediator of splanchnic arterial vasodilation or antagonist of the effects of vasoconstrictor systems in the kidney has been proposed 48, 49. Taken together, these findings indicate that changes in the systemic arterial circulation of patients with type 1 and type 2 HRS are qualitatively similar but of different intensity.…”
Section: Discussionmentioning
confidence: 90%
“…For example, in transgenic animals overexpressing ANP, salt is retained despite the increased plasma ANP 7–10. In heart failure, plasma levels of ANP are markedly increased, yet sodium is retained 11–13. The mechanism underlying such apparent renal insensitivity to ANP is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…kidney; sildenafil; viagra; ANP; renin A RELATIVE RESISTANCE TO THE natriuretic action of atrial natriuretic peptide (ANP) has been observed in sodium-retaining conditions such as nephrotic syndrome (40), congestive heart failure (35), and, in particular, cirrhosis of the liver. In liver cirrhosis the normal natriuretic effect of endogenous ANP or exogenously administered ANP 99 -126 is blunted (12,22,33,42). This phenomenon cannot be explained by the existence of a modified or less biologically active peptide in cirrhosis (17,38).…”
mentioning
confidence: 95%
“…In liver cirrhosis the normal natriuretic effect of endogenous ANP or exogenously administered ANP 99 -126 is blunted (12,22,33,42). This phenomenon cannot be explained by the existence of a modified or less biologically active peptide in cirrhosis (17,38).…”
mentioning
confidence: 95%